Poverty predictors in the Czech Republic: do health predictors also matter?. (28th February 2019) - Krůtilová, Veronika Koči; Hazuchova, Nad'a
Abstract : Poverty has been investigated from various perspectives. Less attention has been paid to the health dimension however. The aim of the paper is to determine the impact of health predictors on poverty in the Czech Republic. Data from the Statistics on Income and Living Conditions and the method of logistic regression is used. We found that poverty is associated with health issues. Unmet need for healthcare services is a significant predictor of all observed types of poverty. The presence of health problems limiting individual's activities is associated with a risk of material deprivation and consistent poverty.